The Role Of Cost Accounting In Supporting National Health Financing Policy - Sara Aprilia Siregar siregar; Kevin Fritson Napitupulu; Juwita Maharani; Dwi Noerjoedianto; Adilla Solida (CV. AFDIFAL MAJU BERKAH, 2026)
Health financing plays a crucial role in ensuring the sustainability of the national health system, particularly in the implementation of the National Health Insurance (JKN). The implementation of a prospective payment system based on Indonesian Case-Based Groups (INA-CBGs) requires accurate cost information to ensure efficient and equitable health financing policies. Cost accounting is a crucial tool in providing information on health care costs. This study aims to examine the role of cost accounting in supporting national health financing policies through a Systematic Literature Review (SLR) approach. The study analyzed 16 national and international scientific articles using thematic synthesis. The study results indicate that cost accounting supports the determination of healthcare service tariffs, increased financing efficiency, cost control, and the implementation of the National Health Insurance (JKN) policy and the achievement of Universal Health Coverage. However, its implementation still faces challenges related to information systems and human resource capacity. Therefore, strengthening cost accounting is necessary as part of national healthcare financing reform.